A laser-driven droplet source for plasma physics applications. (11th December 2020) - Aurand, Bastian; Aktan, Esin; Schwind, Kerstin Maria; Prasad, Rajendra; Cerchez, Mirela; Toncian, Toma; Willi, Oswald
Abstract: In this paper, we report on the acceleration of protons and oxygen ions from tens of micrometer large water droplets by a high-intensity laser in the range of 10 20 W/cm 2 . Proton energies of up to 6 MeV were obtained from a hybrid acceleration regime between classical Coulomb explosion and shocks. Besides the known thermal energy spectrum, a collective acceleration of oxygen ions of different charge states is observed. 3D PIC simulations and analytical models are employed to support the experiential findings and reveal the potential for further applications and studies.